A Study of the Effects of some Water Plant Extracts on the killing Rates of the Two insects Trogoderma granarium Everts Dermestidae : Coleoptera and Oryzaephilus surinamensis (L.) Silvanidae : Coleoptera - Othman, Nada Sabeeh (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted to show the effects of some water plant extracts of leaves of the plants, Myrtle Myrtus communis L. , Rue Ruta graveolens L. , Rosemary Rosemarinus officanalsi , Basil Ocimum basilicum and Mint Mentha piperita L. with the concentrations 1, 4, 7, 9 % on calculating the death rates of both Trogoderma granarium Everts and the adults of Oryzaephilus surinamensis (L.). It was found that the concentrations 7% and 9% of M. communis and the concentration 9% of R. graveolens gave the highest average of death rate for the larvae of T. granarium which was 100%. The concentration 7% of R. graveolens extract and 9% of M. piperita gave high death averages to be 96.67 and 93.33% respectively. The relative average was 1000 for R. graveolens and was 285 for M. piperita. The insect T. granarium recorded the concentrations 7% and 9% for the extracts of M. communis , R. graveolens and M. piperita with high death average rates to be 100%. M. piperita and R. graveolens gave the highest efficiency rates which were 883 and 662, while the extract of R. officanalsi recorded a lowest death rate to be 100 % for each of the two insects T. granarium and O. surinamensis